Memahami Zakat Profesi dan Kemudahan Zakat Online - Athallah, Muhammad Farhan (Maliki Interdisciplinary Journal, 2025)
Zakat is an Islamic pillar for social justice and economic equality. This article examines professional zakat, a jurisprudential adaptation to modern income, and online zakat, an innovation simplifying payment and fund distribution. This literature review analyzes their concepts, challenges, and prospects. Findings indicate that despite challenges like low awareness and differing fatwas for professional zakat, and data security and digital divide issues for online zakat, both hold promising prospects. The growth in professionals and digital integration significantly optimize zakat’s role in social justice and sustainable economic development in the digital era.